Manajemen Peserta Didik Dan Penguatan Karakter Religius Melalui Pembelajaran Kitab Kuning Studi MAN 3 Kandangan Kediri, Indonesia - Mustajib Mustajib; Prim Masrokan Mutohar; Imam Fuadi (El-Idare, 2022)
This article aims to find out the management of students and the strengthening of religious character through learning the yellow book. Is a type of qualitative descriptive research. Sources of information from this study were school principals, subject teachers, deputy curricula, guidance counselors and school students and school cooperative guards concerned. The method used is a qualitative method of case study research. The techniques used in data collection were carried out through non-participatory observation, interviews, and documentation using data analysis which was carried out continuously from the beginning to the end of the study starting from collecting data, data reduction, data presentation and drawing conclusions. Observation temporary results show that the implementation is applied in strengthening religious character through the yellow book subjects carried out in the madrasa program.